Tracheal Agenesis: A Challenging Prenatal Diagnosis—Contribution of Fetal MRI - Charline Bertholdt; Estelle Perdriolle-Galet; Pascale Bach-Segura; Olivier Morel (Case Reports in Obstetrics and Gynecology)
Tracheal agenesis is a rare congenital anomaly. The prevalence is less than 1 : 50 000 with a male to female ratio of 2 : 1. This anomaly may be isolated but, in 93% of cases, it is part of polymalformative syndrome. The most evocative diagnosis situation is the ultrasonographic congenital high airway obstruction syndrome. Dilated airways, enlarged lungs with flattened diaphragm, fetal ascites and severe nonimmune hydrops can be observed. In the absence of a congenital high airway obstruction syndrome, the antenatal diagnosis of tracheal agenesis is difficult. Tracheal agenesis should be suspected in the presence of an unexplained polyhydramnios associated with congenital malformations. The fetal airway exploration should then be systematically performed by fetal thoracic magnetic resonance imaging. A case of Floyd’s type II tracheal agenesis, detected during the postnatal period, is reported here. The retrospective reexamination of fetal magnetic resonance images showed that the antenatal diagnosis would have been easy if a systematical examination of upper airways had been performed. Prenatal diagnosis of tracheal agenesis is possible with fetal MRI but the really challenge is to think about this pathology.